2022
DOI: 10.1080/21655979.2022.2053803
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0002360 regulates the Taxol resistance and malignant behaviors of Taxol-resistant non-small cell lung cancer cells by microRNA-585-3p-dependent modulation of G protein regulated inducer of neurite outgrowth 1

Abstract: Drug resistance has become the major obstacle for the treatment of non-small cell lung cancer (NSCLC). Circular RNAs (circRNAs) are tightly linked to the development of drug resistance of NSCLC. Herein, we tested the function of circ_0002360 in the Taxol resistance of NSCLC. Circ_0002360, microRNA (miR)-585-3p and G protein regulated inducer of neurite outgrowth 1 (GPRIN1) were quantified by quantitative real-time PCR (qRT-PCR). To identify the circular structure of circ_0002360, RNase R digestion was applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Cui et al . proved that circ_0002360 can regulate paclitaxel resistance in NSCLC through G protein-regulated inducer of neurite outgrowth 1 (GPRIN1) and GPRIN1 was overexpressed in paclitaxel-\resistant H1299 cell lines compared to the sensitive cells [37]. GNB2 was a guanine nucleotide-binding protein (G proteins), encoding for beta subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al . proved that circ_0002360 can regulate paclitaxel resistance in NSCLC through G protein-regulated inducer of neurite outgrowth 1 (GPRIN1) and GPRIN1 was overexpressed in paclitaxel-\resistant H1299 cell lines compared to the sensitive cells [37]. GNB2 was a guanine nucleotide-binding protein (G proteins), encoding for beta subunit.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that circRNAs play important roles in tumor malignancy, including tumor proliferation, metastasis, chemosensitivity, and radiosensitivity [22]. The mechanism of circRNA involvement in tumor chemotherapy sensitivity has been a hot topic in recent years, suggesting the potential of circRNAs as new tools to improve tumor chemosensitivity [23][24][25]. However, the role and mechanisms of circRNAs in HNSCC chemosensitivity remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them function as sponges and stabilizers of specific miRNAs because they have more than one site to recognize and bind specific miRNA; this function can reduce the number of functional miRNA and regulate the potential MDR-associated factors under regulation of this miRNA 103 , 104 , 105 , 106 , 107 , 108 . For example, circ_0002360 are found intimately linked to the development of drug resistance of NSCLC, through the potential mechanisms to modulate miR-585-3p/G protein regulated inducer of neurite outgrowth 1 (GPRIN1) axis 121 . Hsa_circ_0000277 promoted esophageal squamous cell carcinoma (ESCC) progression and cisplatin (DDP) resistance via modulating miR-873-5p/SOX4/Wnt/ β -catenin axis 122 .…”
Section: Mechanisms For Regulation Of the Mdr-associated Factors Or S...mentioning
confidence: 99%